The role of negative affects as mediators in the relationship between stress and mental health in Ecuadorian adolescents - Moreta-Herrera R.; Zumba-Tello D.; de Frutos-Lucas J.; Llerena-Freire S.; Salinas-Palma A.; Trucharte-Martínez A. (My University, 2023)
Background Stress and negative emotions have adverse consequences for the mental health of adolescents, an area that deserves further examination. These attributes are associated with each other and regularly interact in different ways. The way they exert an influence can be both direct and indirect, so the general objective is to elucidate the potential mediating effect of negative affects in the relationship between stress and mental health in Ecuadorian adolescents. participants and procedure An explanatory and mediation design based on structural equation modeling (SEM) was applied with 1154 high school students from Ecuador (67.7% women) aged 14 to 19 years (M = 15.69). results In our sample, the presence of stress and negative affect is moderate, while that of mental health problems is low. According to our final model, these variables covary with and influence each other in the following way: stress (X) has a direct effect on mental health (Y) and also an indirect effect mediated by negative affect (M). The structural regression model proposed explains 63.0% of the variance in mental health. conclusions Stress exerts a relevant impact on mental health, both through direct and indirect pathways. The indirect pathway, mediated by negative affect, opens the door to novel interventional strategies to foster mental health. © 2023 Termedia Publishing House Ltd.. All rights reserved
Keywords: Brands; Logos; Participatory design; Technological tools